Smart Automatic Fish Feeder - Premalatha, K; Maithili, P; Nandhini, JJ (International Journal of Computer Sciences and Engineering, 2025)
This paper deals with the design of smart fish feeder system for the application of home aquarium. An automatic fish feeder is a device/product which provides the right amount of fish food at a predetermined time and it helps the aquarist to feed their pet fish when on a vacation or too busy to maintain a regular feeding schedule. It also ensures their pet fishes are fed in healthy way and on time. The aquarist can set the daily feeding time, feeding amount, number of repetition with time delay and also other optional limits. It can repeat its task accurately on daily basis. Further, the system is smartly monitored for the feed level and details are send to the aquarist via Short Message Service (SMS). The whole process uses electro mechanical feeding and feedback control mechanism with PIC microcontroller incorporated with Global System for Mobile Communication Modem (GSM) and a miniature seed sprayer model, an ultrasonic sensor-warning system. This mechanism is actuated by relay with gear motor.